Enlarged Details and Close-up Views: Art Reproduction in 1930s Czechoslovakia - Buddeus, Hana (Artium Quaestiones, 2022)
Each photograph captures an artwork within a particular frame of space and time, providing a perspective that is contingent and dependent on the era the photograph was made in (Bergstein 1992). Moreover, every photograph is always embedded in specific material conditions and has its own social life (Edwards–Hart 2004). The aim of this article is to show the particularity of reproductions of artworks in 1930s Czechoslovakia and the motivations and discussions behind the extensive use of detail. I argue that the pronounced interest in close-up views is a result of a series of circumstances specific to the period. There is an important pre-condition in the development in the field of art photography and graphic design that took place in the late 1920s, bringing about an interest in sharp and faithful images and full bleed prints, as well as a recognition of the social impact of the medium. As a result, photographers, artists, art historians, and graphic designers living in Czechoslovakia also began to rethink the use of photography in the art field. This was manifested in period publications such as the well-known Fotografie vidí povrch (Photography Sees the Surface), published in 1935. In terms of art reproductions, it shows the importance of close-up views for providing an insight into individual artistic approaches and into the history of the respective artwork. The same year saw the publication of the 31st volume of the art magazine Volné směry, which enables us to follow several micro-histories that can also be applied more generally to the period discussions. As illustrated by a text by Bohuslav Slánský and the reproduced photographs of medieval panel portraits from Karlštejn Castle attributed to Master Theodoric, one of the purposes behind the commissions of enlarged photographic details of artworks were planned restorations. Moreover, examples from the photographic campaigns led by the company of Jan Štenc, the State Photo-Measurement Institute, or the project by Karel Šourek, Alexandr Paul, and František Illek (Documenta Bohemia Artis Phototypica) show that detail is generally used for showing the structure and texture of the work, for zooming in on otherwise distant works, or for the purpose of comparison. According to Volné směry editor-in-chief Emil Filla and his manifesto article “Práce oka”, the new method of working with reproductions and the frequent use of photographic detail precipitated a change in the observational habits of the audience. This intention was materialised through his long-term collaboration with the photographer Josef Sudek, who helped him show the artworks in a new light. It is evident that by the mid-1930s, the synergic work of individuals from different fields brought the use of detail in art-related publications to an unprecedented level.